Investigation of Experimental Studies Focusing on Child-Centered Play Therapy with Document Analysis Technique - Yağmur Ulusoy Doğmuş; Betül Sertkaya (e-Kafkas Eğitim Araştırmaları Dergisi)
Child-centered play therapy is the most frequently preferred therapeutic approach by therapists working with children. This frequently preferred approach has attracted the attention of researchers, so interest in studies demonstrating the effectiveness of child-centered play therapy is increasing daily. The aim of this study was to examine and review the distribution of studies focusing on child-centered play therapy published in Turkish and English, indexed in the Dergipark, YökTez, Eric, and ProQuest databases between 2001 and 2022, according to the research topic, year of publication, sample group and place of publication. This study used document analysis to provide an overview and enable cross-cultural comparison. As a result of the scans, a total of 76 studies were conducted. The studies included in the research were categorized according to the research topic, age group, and intervention method. In national and international publications, internalized and externalized behaviors are the most frequently focused research topics. Social-emotional development ranked second, other problem behaviors ranked third, and academic achievement ranked last. In addition, these studies often included interventions in sample groups of children aged 6--8 years, and individual interventions were preferred over group studies. This study revealed that after 2012, both in Turkey and in many countries around the world, the number of studies focusing on child-centered play therapy increased significantly. These findings were discussed in light of the literature, and various suggestions were made for practitioners and researchers.